PENYELESAIAN SENGKETA BATAS TANAH DALAM PEMBUATAN SERTIFIKAT HAK MILIK ATAS TANAH MELALUI MEDIASI DI ATR/BPN KABUPATEN PASAMAN BARAT - Apriella Desera Genada; Maryati Bachtiar; Meriza Elpha Darnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The location of land boundaries can certainly lead to land disputes that arecontrary to regulations. It is clear that the Regulation of the State Minister for AgrarianAffairs/Head of BPN Number 3 of 1997 and the Implementation Provisions for GovernmentRegulation Number 24 of 1997 Concerning Land Registration states that land registration forthe first time, one of which must collect physical data and land juridical data and severalstages that must be carried out, where The collection and processing of land physical data iscarried out by measuring and mapping the determination of boundaries of land parcels by theNational Land Agency, but there are still individuals who collect and process physical dataunilaterally which results in disputes over land boundaries. The purpose of this study was tofind out the resolution of land boundary disputes in making land ownership certificatesthrough mediation at ATR/BPN in West Pasaman Regency. As well as to find out what thereasons for setting land boundaries in making certificates of ownership rights to land cancause disputes in West Pasaman Regency.The research method used in this study is the sociological method. This research wasconducted at ATR/BPN West Pasaman Regency which was the object of this research case.Then the population and sample are several parties related to the problem under study, aswell as data sources used primary data, secondary data and tertiary data. Data collectiontechniques in this study were interviews, observation and literature review.The conclusions obtained from the research results are First, the settlement of land boundarydisputes in making certificates of ownership rights to land is carried out by mediation 3(three) times carried out by the West Pasaman Regency Land Office as a mediator. Second,the factor causing land disputes in West Pasaman Regency, namely: (a) conflict of interest;(b) structural conflict; (c) value conflict; (d) relationship conflict; and (e) data conflict. Thesuggestions in this writing are First, the applicant for the certificate should be more thoroughand examine the truth about the location of the northern boundary of the land so that landdisputes do not occur with neighbors or residents who are next to our land. Second, the WestPasaman District Land Office should conduct education and socialization regarding landregistration to the public so that land disputes do not occur again in West Pasaman.Keywords: Dispute Resolution-Land Boundaries-Mediation